2019
DOI: 10.15414/jmbfs.2019.9.2.204-207
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Bisphenol a During Submerged Cultivation of Trametes Versicolor

Abstract: Bisphenol A is a persistent chemical, which is widely distributed in the environment despite its short half-life. The continuous release of BPA may cause a chronical exposition of the organisms during sensitive life stages. The chemical possesses not only endocrine disrupting functions but also by oxidative stress may cause damage to the liver cells. In this study the ability of Trametes versicolor 8979 to degrade Bisphenol A during submerged cultivation was exanimated. The chemical was introduced to the mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…It is a well-known medicinal macromycete due to many bioactive components which could have an impact on maintaining human health [ 10 ]. In our previous research, the mycoremediation capacity of T. versicolor NBIMCC 8939 and its ability to degrade lignocellulose and various polycyclic aromatic hydrocarbons were revealed [ 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is a well-known medicinal macromycete due to many bioactive components which could have an impact on maintaining human health [ 10 ]. In our previous research, the mycoremediation capacity of T. versicolor NBIMCC 8939 and its ability to degrade lignocellulose and various polycyclic aromatic hydrocarbons were revealed [ 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of these fungal strains secrete up to three extracellular enzymes involved in EDC decomposition (Bending et al 2002;Takamiya et al 2008). It can be noted from Table 2 that T. versicolor reached a substantial reduction (> 80%) for most tested EDC (Llorca et al 2017;Pezzella et al 2017;Brazkova 2019) and up to 100% for BPA (Pezzella et al 2017). However, the remaining Pleurotus ostreatus and P. chrysosporium species, despite having a different combination of LMEs, also achieved high removal rates from 60 to over 90% (Pezzella et al 2017;Křesinová et al 2018).…”
Section: Potential Of Wrf To Remove Bpa Bps and Np From Wastewatermentioning
confidence: 99%
“…It results from the hydrophobic character of these compounds (log k ow ≥ 3.2), which determines the adsorption behavior of EDCs (Krupadam et al 2011 ). Most of the studies have mainly revealed EDC removal from the aqueous phase without monitoring the extent of biosorption (Pezzella et al 2017 ; Mtibaà et al 2018 ; Brazkova 2019 ). It creates difficulties in assessing the relative contribution of biosorption and biodegradation to the general removal of the highly hydrophobic EDC.…”
Section: Potential Of Wrf To Remove Bpa Bps and Np From Wastewatermentioning
confidence: 99%
“…The strain used in the current study, Trametes versicolor NBIMCC 8939, is known for its ability to degrade industrial dyes, endocrine disrupting chemicals (like bisphenol A), phenolic compounds, PAHs [10][11][12][13] due to the enzymes present in the lignin-modifying complex of the fungus, namely laccase and manganesedependant peroxidase (MnP). The strain was cultivated in submerged conditions and pyrene was introduced in different concentrations in the nutrient medium.…”
Section: Introductionmentioning
confidence: 99%